THE EXPOSITION OF THE HIDDEN STORY OF POST-COLONIAL INDIA WITH REFERENCE TO SHIV K. KUMAR’S THE TRAIN TO DELHI. (International Journal of Food and Nutritional Sciences, 2022)
The Indian English novelist Shiv K. Kumar‟s novel The Train to Delhi mirrors the religious conflict between the Hindus and the Muslims after the Indian Partition in 1947. The Postcolonial India was torn by riots, rampant killings and sexual assault. Quite often, the common people and the innocent become the victims of the religious conflict. The novelist‟s agony over the trouble and restless Postcolonial India and the plight of the women find an echo in the novel. The novel also gives a vivid picture of forceful migration that has enforced the migrants to leave their homes and valuable property behind to save their lives. The novelist condemns the violence against women for being raped, abducted and force them into prostitution. Shiv K. Kumar criticises the Press and the Media for being biased and connivant reporting the fabricated news. Corruption has reigned every department of the Postcolonial India. As it has deep rooted in every field, the social evil couldn‟t still be rooted out from India. Shiv K. Kumar dreams for a country where the women are free from violence and oppression and enjoy social, political and cultural entity and freedom to emerge as empowered individuals. He envisages an India that provides the choice of marriage to women. The novel is a plea to rebuild India with love, compassion, equality and unity despite social, political, linguistic, cultural and religious differences.